A numerical study on hydraulic resistance in flow with vegetation patch. (1st November 2022) - Jahadi, Mahsa; Afzalimehr, Hossein; Ashrafizaadeh, Mahmud; Kumar, Bimlesh
ABSTRACT: The submerged vegetation patch affects the flow structure significantly. Quantifying this structure, which is crucial for river engineers, depends on estimating the drag coefficient accurately. However, most of the available empirical and semi-empirical relations have some uncertainties. So, the present work attempts to estimate and evaluate the drag coefficient by a theoretically based relation. The Reynolds Stress Model (RSM) and the porous zone model in CFD software have been employed to achieve the objectives. Finally, the results show that the theoretical equation presents a proper agreement with the drag coefficient, which is computed using the boundary layer method. However, the empirical equation cannot show the variation of hydraulic resistance along with the vegetation patch. The flow structure simulated by these models presents a reasonable agreement with the measured data in our experimental flume, showing some small deviation between the model and the experimental data, especially inside the canopy. This deviation might be related to the inability of the porous zone model to simulate the wake and the flow separation within the vegetation and downstream of the patch.